Threshold of surface erosion of cohesive sediments - Chen, Dake; Zheng, Jinhai; Zhang, Chi; Guan, Dawei; Li, Yuan; Huang, Huiming (Frontiers in Marine Science, 2022)
Cohesive sediment is ubiquitous in aquatic systems, which often forms fractal aggregates due to cohesive and adhesive forces between particles and is generally eroded as aggregates at low bed shear stresses. The erosion of aggregates plays a significant role in cohesive sediment dynamics. However, the effects of fractal bed aggregation on the erosion threshold of sediment have not been well understood. The incipient motion condition of cohesive sediment is investigated, in which particle aggregation is taken into account by employing the fractal theory and the van der Waals force between particles. A formula for the critical shear stress for surface erosion of cohesive sediments composed of fractal aggregates is developed based on the balance analysis of momentums acting on an aggregate in the bed surface. The developed formula has been successfully applied to different kinds of cohesive sediment. The fractal dimension is found as a function of the solid volume fraction and the diameter of primary particles. The contribution rate of the effective weight of aggregate to the erosion threshold of cohesive sediment is quantified.